Characterization and exposure assessment of household fine particulate matter pollution in China. (20th April 2021) - Yang, Yu‐yan; Fan, Lin; Wang, Jiao; Zhu, Yuan‐duo; Li, Xu; Wang, Xin‐qi; Yan, Xu; Li, Li; Zhang, Yu‐jing; Yang, Wen‐jing; Yao, Xiao‐yuan; Wang, Xian‐liang
Abstract: Household fine particulate matter (PM2.5 ) pollution greatly impacts residents' health. To explore the current national situation of household PM2.5 pollution in China, a study was conducted based on literature published from 1998 to 2018. After extracting data from the literature in conformity with the requirements, the nationwide household‐weighted mean concentration of household PM2.5 (HPL) was calculated. Subgroup analyses of spatial, geographic, and temporal differences were also done. The estimated overall HPL in China was 132.2 ± 117.7 μg/m 3 . HPL in the rural area (164.3 ± 104.5 μg/m 3 ) was higher than that in the urban area (123.9 ± 122.3 μg/m 3 ). For HPLs of indoor sampling sites, the kitchen was the highest, followed by the bedroom and living room. There were significant differences of geographic distributions. The HPLs in the South were higher than the North in four seasons. The inhaled dose of household PM2.5 among school‐age children differed from provinces with the highest dose up to 5.9 μg/(kg·d). Countermeasures should be carried out to reduce indoor pollution and safeguard health urgently.